Pengembangan Bahan Ajar Qira'ah Menggunakan Kitab Baina Yadaik Dengan Model Inside Outside Circle di MTs Lubuklinggau - Fajriyah, Arika Falakul; Imron, Kristina; Irmansyah, Irmansyah (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2025)
The teaching of qirÄâ€™ah (reading) in Arabic education faces several challenges, particularly the lack of innovative methods and learning materials that engage students in contextual reading. This research aims to develop a qirÄâ€™ah teaching material based on Baina Yadaik integrated with the Inside Outside Circle (IOC) learning model at MTs Ittihadul Ulum Lubuklinggau. The research employs a Research and Development (R&D) method using a simplified version of the Borg & Gall model, involving stages such as potential and problem analysis, data collection, product design, validation, revision, and limited trials. The findings indicate a significant improvement in students' reading abilities after using the developed material, demonstrating the effectiveness of the IOC model in enhancing interaction, comprehension, and vocabulary mastery. This study concludes that integrating IOC with Baina Yadaik not only improves students' reading skills but also provides a model for innovative, student-centered Arabic language teaching. Future studies could explore the application of this method in other schools or educational contexts